The search - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2000)
Sarah Patrick is being forced to take part in a deadly mission by a man who knows enough about her past to ensure her cooperation. John Logan - a man who won't take no for an answer. As part of an elite K-9 search and rescue team, Sarah and her golden retriever Monty, have a gift for finding what no one else can - whether it's a survivor buried alive by an earthquake or the skeleton of a murdered child. Once Sarah starts the perilous assignment, she realises Logan's promise that she will be safe may not be enough to protect her. Because a killer is devising a sadistic vengeance...and he may soon find a chilling use for Sarah..